Comparing the effectiveness of schema therapy and solution-oriented therapy on marital satisfaction of couples applying for divorce - Langari, Mohammad Reza; Mafakheri, Abdollah; Bakhshipour , Abolfazl (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: This research was conducted to compare the effectiveness of schema therapy and solution-oriented therapy in improving the marital satisfaction of couples applying for divorce.Methods and Materials: In this research, a quasi-experimental design with pre-test, post-test and follow-up was used. The statistical population included all divorce applicants in Bojnord city in 2021 who had applied to the court of justice of this city. The statistical sample included 48 people who were selected as available sampling. Then, they were replaced randomly into 3 groups: schema therapy (8 couples), solution-oriented therapy group (8 couples) and control group (8 couples). The data collection tool was Enrich Marital Satisfaction Questionnaire (1989). The data was analyzed by repeated measures analysis of variance in SPSS.Findings: The results of the research showed that there is a significant difference between the mean of pre-test and post-test scores of the experimental and control groups (P<0.01). That is, both treatment methods had a significant effect in improving couples' satisfaction. Also, comparing the means of experimental groups indicated no significant difference between schema therapy and solution-oriented therapy in improving couples' satisfaction (P<0.05). Also, in the follow-up period, compared to the pre-te st and post-test, the effect of reducing dissatisfaction was significant.Conclusion: Based on the obtained results, it can be said that schema therapy and solution-oriented therapy can improve satisfaction and improve the relationship of couples seeking divorce